Pengaruh Gaya Kepemimpinan Situasional, Motivasi Kerja, Dan Locus Of Control Terhadap Prestasi Kerja Karyawan Perusahaan Daerah Air Minum (PDAM) Kabupaten Bantul Yogyakarta - Miftahul Janah Rosmayanti (JURNAL EKOBIS DEWANTARA, 2018)
Abstract The purpose of this research is to know (1) influence of Situational leadership style toward employee performance, (2) influence of Work Motivation to employee performance, (3) influence of Locus Of Control on employee performance, and (4) influence of Situational Leadership Style, Work Motivation and Locus of Control have a significant effect on the work performance of PDAM Employees of Bantul Regency Yogyakarta. This research belongs to the type of causal causal research. The population is all employees of PDAM Bantul district, amounting to 220 people and 20% of the number of employees is 44 people who will be used as a sample. Method of data retrieval was questionnaire, while data analysis technique using multiple linear regression analysis was supported by F (F-Test) and T (T-Test) test and classical assumption test consist of normality test, multicollinearity test, and heteroscedasticity test. The results showed that there is influence Situational Leadership Style (X1) on work performance (Y) with significance value = 0.035 <α = 0.05. There is influence of Work Motivation (X2) to work performance (Y) with significance value = 0.127 <α = 0.05. There is influence of Locus of Control (X3) on work performance (Y) with significance value = 0.044 <α = 0.05. Situational Leadership Style (X1), Work Motivation (X2) and Locus of Control (X3) have an effect on Work Achievement (Y) simultaneously because the value of sig 0,000 <0,05. Keywords : situational leadership style (X1), work motivation (X2), locus of control (X3), work performance (Y)